Experiences of Violence and Mental Health Outcomes among Colombian Men who have Sex with Men (MSM) and Transgender Women - Zea, Maria Cecilia (Journal of interpersonal violence, 2022)
Colombia endured 70 years of internal conflict, but despite a peace agreement, violence continues to be significant in the post-conflict era. Violence degrades the health and well-being of affected populations and it engenders psychological distress. Little is known about the impact of violence on the mental health of sexual and gender minority populations in Colombia. This study aimed to examine the frequency and sources of violence among cisgender men who have sex with men (MSM) and transgender women and their association with depressive symptoms and substance use. We administered a survey to 942 MSM and 58 transgender women recruited using respondent-driven sampling. We estimated the relationship between mental health indicators and experiences of violence using stepwise logistic and linear regressions, controlling for income, education, age, race, and mistreatment for being effeminate when younger. Respondent-driven sampling adjusted prevalence of any type of violence was 60.9% for the total sample, 59.8% for MSM, and 75.1% for transgender women. Experiences of violence were significantly related to depressive symptoms, binge drinking and drug use for the MSM sample. Violence perpetrated by family members or acquaintances was associated with greater depressive symptoms, and violence perpetrated by partners and strangers was associated with increased binge drinking and drug use. These results provide significant evidence of the negative association of experiences of violence and the mental health of sexual and gender minority people, a vulnerable population in Colombia. This study addresses issues of diversity regarding sexual orientation and gender identity in a Latin American middle-income country.